Body Dissatisfaction and Social Anxiety Among Female University Students: Ketidakpuasan terhadap Tubuh dan Kecemasan Sosial di Kalangan Mahasiswi Perguruan Tinggi - Mardianti, Hestiana Rovita Endah Wita; Widyastuti, Widyastuti (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: Early adulthood is a critical stage where individuals experience major developmental, psychological, and social transitions. Specific Background: Female students are particularly vulnerable to social anxiety and body dissatisfaction due to social and cultural expectations about appearance. Knowledge Gap: Despite increasing concerns about these issues, research focusing on their relationship in Indonesian higher education contexts is limited. Aims: This study aims to examine the relationship between body dissatisfaction and social anxiety among female students at Muhammadiyah University of Sidoarjo. Results: Using a quantitative correlational design with 150 participants, body dissatisfaction was measured with the Multidimensional Body-Self Relations Questionnaire–Appearance, and social anxiety with the Social Anxiety Scale by La Greca and Lopez. Data analysis using Pearson Product Moment showed a significant positive correlation (r = 0.653, p < 0.001). Novelty: The findings highlight how body dissatisfaction significantly contributes to social anxiety, explaining 42% of its variance, specifically within the Indonesian female student population. Implications: These results provide empirical evidence to develop intervention programs in higher education aimed at reducing body dissatisfaction and social anxiety, thereby promoting mental health and well-being among female students. Highlights: Significant correlation between body dissatisfaction and social anxiety Female university students as a vulnerable group Contribution of body dissatisfaction to social anxiety variance Keyword: Body Dissatisfaction, Social Anxiety, Female Students, Higher Education, Mental Health